A energia e suas implicações no ensino-aprendizagem da química - Silva Junior, Carlos Neco da (2010)
The area of Education in Chemistry in Brazil has appeared over 30 years and its growth has been accelerated by the need of comprehension of the processes of teaching and learning in chemistry. Many researches, in this area, has among its investigation objects the teaching tools like teaching materials and the learning processes of students in high school and basic education, but when dealing with higher levels of education, they are seldom portrayed. This study aimed to investigate the General Chemistry textbooks with respect to approach the concept of energy; know the main ideas of graduate students in Chemistry on the relation of the concept of energy and chemical transformations; finally, developing a cicle of studies with the proposition of an approach wich inter-relate the concept of energy and its implications in the teaching-learning process of a chemical transformation. To do so, we used as instruments a questionnaire, press conference, conceptual map and experimental activities. All activities of the study cicle were videotaped and recorded, transcribed and the results organized in tables. For the activities of the study cicle texts that have been developed and inter-relating concepts of chemistry and energy, which in turn gave theoretical support to the activities in the cycle. In the analysis it was used as a theoretical content the analysis of Laurence Bardin. The results revealed that the analysis of the book might be perceived that not always the concept of energy is used in order to generate the abstract thought of chemical transformations, but that the main macroscopic thermodynamic variables are present in the explanation of these transformations. During the study cicle, were studied two chemical reactions: the first one, made possible to approach the macroscopic dimension to quantify the concept of energy and the second one, made possible to demonstrate the macro and microscopic dimension of the concept of energy during a chemical transformation. In all reactions proposed, students used, in most of the times, as explanations, only macroscopic observations of the reactions under study and failed to realize that the concept of energy can be used to explain macro and microscopic chemical transformation. As a final action of the study cicle, students requested further discussion, to clarify the link between the concept of energy and the meanings constructed in the process of studying the reactions. This is done through an oral explanation, during the cycle, and registered in this thesis and attempts to show the interrelationship existing conceptual